Method for improving surface roughness of dry-jet wet spinning polyacrylonitrile precursor
By performing surface etching of water-containing expanded PAN raw wire, the problems of small contact area and poor adhesion between dry-sprayed wet spinning carbon fiber and resin material are solved, the surface roughness of carbon fiber and coupling ability with resin are improved, and its application is expanded Scene.
Patent Information
- Application Number
- CN202411299125.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-18
AI Technical Summary
When forming composite materials with resin, the smooth surface of dry-sprayed wet spinning carbon fiber has problems such as small contact area, low interlayer shear strength, and poor adhesiveness of composite interfaces, resulting in a degradation of comprehensive performance.
By surface etching of the water-containing expanded PAN raw wire, the surface roughness of the raw wire is improved, and PAN raw wire with deep surface gullies is prepared, thereby improving the coupling ability of dry-sprayed wet spinning carbon fiber and resin material. Specific steps include copolymerization, desilverization, solidification bath, water washing, surface etching, water washing drafting, drying densification and steam drafting.
It improves the surface roughness of carbon fiber, enhances its coupling ability with resin materials, and expands application scenarios.
Smart Images

Figure CN119243355A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber manufacturing and relates to a method for improving the surface roughness of dry-jet wet-spun polyacrylonitrile precursor. Background Art
[0002] Carbon fiber is a polymer fiber material with a carbon content of more than 90%. It has the characteristics of high strength, high modulus, acid and alkali resistance, corrosion resistance, etc. It is widely used in aerospace, transportation rail, new energy and other fields. The tensile strength of high-strength and high-modulus carbon fiber exceeds 7000MPa, and the elastic modulus exceeds 350GPa. It has ultra-high stiffness, excellent specific modulus, good environmental stability and dimensional stability. The dry-jet wet spinning process is often used to prepare high-strength and high-modulus carbon fiber. Because the polyacrylonitrile (PAN) stock solution can release stress and allow the solvent to diffuse outward when in the air, it can generate fibers with smoother surfaces and better mechanical properties, and can reduce fiber voids and surface collapse caused by solidification. However, the dry-jet wet-spinning carbon fiber with a smooth surface has problems such as small contact area, low interlayer shear strength, and poor composite interface adhesion in the process of forming a composite material with the resin, which can easily lead to a decrease in comprehensive performance.
[0003] Treating the surface of carbon fiber precursor and body is a method to improve the comprehensive performance of composite materials formed with resin. However, the surface activity of carbon fiber body is weak, and methods such as surface chemical modification and irradiation are costly and inefficient. Surface etching of carbon fiber precursor can significantly improve etching efficiency, increase fiber interface contact area, and improve fiber surface roughness. For example, the literature (Gao Q, Jing M, Chen M, et al. Research on PAN Nascent Fiber Interior Microstructure through Ultrasonic Etching and Ultrathin Sectioning [J]. Polymer Science Series A, 2018, 60 (5): 594-598. DOI: 10.1134 / S0965545X1805005X.) uses strong acid and mixed solvent to perform preliminary surface etching and fiber separation on PAN fiber, forming a clear surface groove structure and microfibril structure. However, this method involves etching after the densification, steam drawing and rolling of the original silk. The original silk has high density, and it is difficult for the etching solvent to penetrate into the fiber. The etching efficiency is not high, and the improvement in roughness is not high enough. Summary of the invention
[0004] The object of the present invention is to provide a method for improving the surface roughness of dry-jet wet-spun polyacrylonitrile precursor fibers, wherein the method improves the surface roughness of the precursor fibers by surface etching of water-swollen PAN precursor fibers, prepares PAN precursor fibers with deep surface grooves, and further prepares carbon fibers with high surface roughness, thereby improving the coupling ability between dry-jet wet-spun carbon fibers and resin materials.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] The method for improving the surface roughness of dry-jet wet-spun polyacrylonitrile precursor comprises the following steps:
[0007] (1) Copolymerization: acrylonitrile and itaconic acid are used as copolymer monomers, one of acrylic acid, methyl acrylate, methyl methacrylate and isobutyl methacrylate is used as the third monomer, and azobisisobutyronitrile is used as the initiator to carry out homogeneous free radical solution polymerization in dimethyl sulfoxide (DMSO) to prepare the spinning solution;
[0008] (2) Degassing: Degassing the spinning solution and sending it to the spinning unit;
[0009] (3) Coagulation bath: The spinning solution after degassing and degassing is extruded from the spinneret into the coagulation bath through a metering pump, and simultaneously drawn in the air to obtain the nascent fiber;
[0010] (4) Washing: The raw fiber is washed with desalted water in multiple stages to remove the solvent, so that the PAN raw fiber reaches an expanded and porous state;
[0011] (5) Surface etching: The fiber after washing and expansion is placed in an etching tank and immersed in an etching solution for surface etching. The mass ratio of the etchant H2SO4 to DMSO in the etching solution is 4 to 5:10, the temperature of the etching tank is 24 to 30°C, and the etching time is 2.0 to 4.3 seconds. After the etching is completed, the etching solution remaining on the fiber is squeezed out by a squeezing roller;
[0012] (6) Water washing and stretching: The fibers after surface etching and extrusion are washed with desalted water in multiple stages to remove the solvent, and then washed with hot water at 60 to 80°C and stretched by 1 to 2 times;
[0013] (7) Drying and densification: After washing and drawing, the fiber is coated with 1-3% silicone oil and dried and densified. The hot roller pressure is 0.45-0.65 MPa, the temperature range is 145-180°C, and the drawing is 1.0-2.0 times;
[0014] (8) Steam drawing: The fibers after drying and densification treatment enter steam drawing and are drawn 2.0 to 3.5 times at a steam pressure of 0.30 to 0.60 MPa to produce dry-jet wet-spun PAN raw fibers with high surface roughness.
[0015] Furthermore, in step (1), the temperature of the homogeneous free radical solution polymerization reaction is 60-65° C., the temperature of the spinning solution is 40-70° C., and the solid content is 14-25%.
[0016] Furthermore, in step (1), taking the total weight of monomers as 100%, the proportion of each monomer is: 92-99.8 wt.% acrylonitrile, 0.1-4 wt.% itaconic acid and 0.1-4 wt.% the third monomer.
[0017] Furthermore, in step (2), the specific method for degassing is as follows: degassing the spinning solution at a pressure of -60 to -78 KPa, and then filtering it through a primary filtration process of 3 μm, degassing the solution after the primary filtration at a pressure of -78 to -100 KPa, and then filtering it through a secondary filtration process of 1 μm before sending it to the spinning unit.
[0018] Furthermore, in step (3), the concentration of DMSO in the coagulation bath is 55-70 wt %, the temperature is 5-25° C., and the draft ratio in air is 1-2.5 times.
[0019] Furthermore, in step (4) or (6), the water washing temperature is controlled at 33-36°C.
[0020] Furthermore, in step (6), the DMSO content in the fiber after washing is ≤0.1%.
[0021] Furthermore, in step (7), the silicone oil agent is the silicone oil agent conventionally used in the oiling stage in the polyacrylonitrile precursor preparation process, for example, the silicone oil agent composed of auxiliary agents such as amino-modified silicone oil, polyether-modified silicone oil, antistatic agent and emulsifier.
[0022] Furthermore, in step (7), the hot roller pressure is 0.45-0.55 MPa, and the temperature range is 146-167°C.
[0023] Furthermore, in step (8), the stretching is 3.3 to 3.5 times.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The present invention improves the surface roughness of the water-swelled porous PAN precursor by surface etching, thereby preparing PAN precursor with deep surface grooves, and further preparing carbon filaments with high surface roughness.
[0026] (2) Carbon filaments with high surface roughness can effectively improve the coupling ability between dry-jet wet-spun carbon fibers and resin materials, thereby expanding their application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the SEM image of the PAN precursor obtained in Example 1;
[0028] Figure 2 This is the SEM image of the PAN precursor obtained in Example 2;
[0029] Figure 3 This is the SEM image of the PAN raw fiber prepared in Comparative Example 4. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] Example 1
[0032] (1) Copolymerization: A mixed solution consisting of 92 wt.% acrylonitrile, 4 wt.% itaconic acid and 4 wt.% methyl methacrylate in dimethyl sulfoxide was subjected to free radical solution polymerization to obtain a polyacrylonitrile high molecular polymer spinning solution with a solid content of 18.5%.
[0033] (2) Degassing: The spinning solution is first degassed in a degassing kettle at a pressure of -76KPa, then degassed at 3μm in a primary filtration process, and then degassed at a pressure of -97KPa in a degassing kettle, and then sent to a 1μm secondary filtration process.
[0034] (3) Coagulation bath: The debonding and degassing spinning solution is pressurized and transported to the spinning unit, and the spinning solution temperature is maintained at 45°C. The spinning solution passes through an air layer and then enters a coagulation bath for coagulation and molding. The air layer is 2 mm, the DMSO concentration in the coagulation bath is 45 wt%, and the coagulation bath temperature is 5°C. At the same time, a drafting multiple of 1.1 is applied to obtain primary fibers.
[0035] (4) Water washing: The raw fiber is subjected to multiple stages of desalted water at 33-36°C to remove the solvent, so that the PAN raw fiber reaches an expanded and porous state.
[0036] (5) Surface etching: The fiber after washing and expansion is placed in an etching tank and immersed in an etching solution for surface etching. The mass ratio of H2SO4 to DMSO in the etching solution is 4:10, the temperature of the etching tank is 30°C, and the immersion time is 4.3 s.
[0037] (6) Water washing and stretching: The etched fiber is passed through multiple stages of desalted water at 33-36°C to remove the solvent, and then washed in hot water at 60-80°C while being stretched at 1.1 times.
[0038] (7) Drying and densification: The fibers after hot water drawing pass through a 1.1% silicone oil bath, and the oiled raw fibers pass through a hot roller with a certain temperature gradient for drying and densification. The drying roller pressure is maintained at 0.45 MPa, there are 25 drying rollers, the drying roller temperature gradient is 4°C, and the temperature range is 146-165°C.
[0039] (8) Steam drawing: The dried fiber tow was steam drawn with a saturated steam pressure of 0.45 MPa and a steam drawing multiple of 3.5 to obtain polyacrylonitrile precursor and test the surface morphology. Obvious longitudinal surface grooves appeared on the precursor, such as Figure 1 shown.
[0040] Example 2
[0041] This embodiment is basically the same as embodiment 1, except that in step (5), surface etching: the mass ratio of H2SO4 to DMSO is 5:10, polyacrylonitrile precursor is obtained and the surface morphology is tested. Obvious grooves appear on the surface of the precursor, and there are fiber splitting and more gel impurities, such as Figure 2 shown.
[0042] Comparative Example 1
[0043] This comparative example is basically the same as Example 1, except that in step (5) surface etching, the mass ratio of H2SO4 to DMSO is 3:10, polyacrylonitrile precursor is obtained and the surface morphology is tested, and the surface of the precursor is smooth without grooves.
[0044] Comparative Example 2
[0045] This comparative example is basically the same as Example 1, except that in step (5) surface etching, the mass ratio of HCl and H3PO4 to DMSO in the etching solution is 2:2:10, polyacrylonitrile precursor is obtained and the surface morphology is tested, and the surface of the precursor becomes rough but has no longitudinal grooves.
[0046] Comparative Example 3
[0047] This comparative example is basically the same as Example 1, except that in step (5) surface etching, the mass ratio of HNO3 to DMSO in the etching solution is 4:10, and the raw silk after etching shows obvious dissolution, and most of the raw silk is washed with water and cannot be dried and steamed.
[0048] Comparative Example 4
[0049] This comparative example is basically the same as Example 1, except that the surface etching step is not performed. The polyacrylonitrile precursor is obtained and the surface morphology is tested. The surface of the precursor is smooth and has no grooves. Figure 3 shown.
[0050] Comparative Example 5
[0051] This comparative example is substantially the same as Example 1, except that the surface of the steam-drawn and wound raw silk is etched, as follows:
[0052] (1) Copolymerization: A mixed solution consisting of 92 wt.% acrylonitrile, 4 wt.% itaconic acid and 4 wt.% methyl methacrylate in dimethyl sulfoxide was subjected to free radical solution polymerization to obtain a polyacrylonitrile high molecular polymer spinning solution with a solid content of 18.5%.
[0053] (2) Degassing: The spinning solution is first degassed in a degassing kettle at a pressure of -76KPa, then degassed at 3μm in a primary filtration process, and then degassed at a pressure of -97KPa in a degassing kettle, and then sent to a 1μm secondary filtration process.
[0054] (3) Coagulation bath: The debonding and degassing spinning solution is pressurized and transported to the spinning unit, and the spinning solution temperature is maintained at 45°C. The spinning solution passes through an air layer and then enters a coagulation bath for coagulation and molding. The air layer is 2 mm, the DMSO concentration in the coagulation bath is 45 wt%, and the coagulation bath temperature is 5°C. At the same time, a drafting multiple of 1.1 is applied to obtain primary fibers.
[0055] (4) Washing and stretching: The spun fiber is passed through multiple stages of desalted water at 33-36°C to remove the solvent, and then washed in hot water at 60-80°C while being stretched at 1.1 times.
[0056] (5) Drying and densification: The fibers after hot water drawing pass through a 1.1% silicone oil bath, and the oiled raw fibers pass through a hot roller with a certain temperature gradient for drying and densification. The drying roller pressure is maintained at 0.45 MPa, there are 25 drying rollers, the drying roller temperature gradient is 4°C, and the temperature range is 146-165°C.
[0057] (6) Steam drawing: The dried fiber bundles were steam drawn, the saturated steam pressure was 0.45 MPa, and the steam drawing multiple was 3.5.
[0058] (7) Surface etching: The rolled raw silk was placed in an etching tank and immersed in an etching solution for surface etching. The mass ratio of H2SO4 to DMSO in the etching solution was 4:10, the etching tank temperature was 30°C, and the immersion time was 4.3s.
[0059] (8) Water washing and stretching: The etched fiber is washed with desalted water at 33-36°C for multiple stages to remove the solvent, and the polyacrylonitrile precursor is obtained and the surface morphology is tested. The surface of the precursor is smooth and has no grooves.
Claims
1. A method for improving the surface roughness of dry-jet wet-spinning polyacrylonitrile precursor, characterized in that: The following steps are involved: (1) Copolymerization: acrylonitrile and itaconic acid are used as copolymer monomers, one of acrylic acid, methyl acrylate, methyl methacrylate and isobutyl methacrylate is used as the third monomer, and azobisisobutyronitrile is used as the initiator to carry out homogeneous free radical solution polymerization in DMSO to prepare the spinning solution; (2) Degassing: Degassing the spinning solution and sending it to the spinning unit; (3) Coagulation bath: The spinning solution after degassing and degassing is extruded from the spinneret into the coagulation bath through a metering pump, and simultaneously drawn in the air to obtain the nascent fiber; (4) Water washing: The raw fiber is washed with desalted water in multiple stages to remove the solvent, so that the PAN raw fiber reaches an expanded and porous state; (5) Surface etching: The fiber after washing and expansion is placed in an etching tank and immersed in an etching solution for surface etching. The mass ratio of the etchant H2SO4 to DMSO in the etching solution is 4-5:10, the temperature of the etching tank is 24-30 °C, and the etching time is 2.0-4.3 s. After the etching is completed, the etching solution remaining on the fiber is squeezed out by a squeezing roller; (6) Water washing and stretching: The fibers after surface etching and extrusion are washed with desalted water in multiple stages to remove the solvent. After washing, they are washed with hot water at 60-80°C and stretched by 1-2 times. (7) Drying and densification: After washing and drawing, the fiber is coated with 1-3% silicone oil and dried and densified. The hot roller pressure is 0.45-0.65 MPa, the temperature range is 145-180 ° C, and the drawing is 1.0-2.0 times; (8) Steam drawing: The fibers after drying and densification treatment enter steam drawing and are drawn 2.0 to 3.5 times at a steam pressure of 0.30 to 0.60 MPa to produce dry-jet wet-spun PAN raw fibers with high surface roughness.
2. The method according to claim 1, characterized in that In step (1), the homogeneous free radical solution polymerization reaction temperature is 60-65°C, the spinning solution temperature is 40-70°C, and the solid content is 14-25%.
3. The method according to claim 1, characterized in that In step (1), taking the total weight of monomers as 100%, the proportion of each monomer is: 92-99.8 wt.% acrylonitrile, 0.1-4 wt.% itaconic acid and 0.1-4 wt.% the third monomer.
4. The method according to claim 1, characterized in that: In step (2), the specific method of removing single atoms and degassing is as follows: removing single atoms from the spinning solution at a pressure of -60 to -78 KPa, and then filtering the solution through a primary filtration process of 3 μm, degassing the solution after the primary filtration process at a pressure of -78 to -100 KPa, and then filtering the solution through a secondary filtration process of 1 μm before delivering it to the spinning unit.
5. The method according to claim 1, characterized in that In step (3), the concentration of DMSO in the coagulation bath is 55-70 wt %, the temperature is 5-25° C., and the stretching multiple in air is 1-2.5 times.
6. The method according to claim 1, characterized in that In step (4) or (6), the water washing temperature is controlled at 33-36°C.
7. The method according to claim 1, characterized in that In step (6), the DMSO content in the fiber after washing is ≤0.1%.
8. The method according to claim 1, characterized in that In step (7), the silicone oil-containing agent is a silicone oil-containing agent composed of amino-modified silicone oil, polyether-modified silicone oil, an antistatic agent and an emulsifier.
9. The method according to claim 1, characterized in that: In step (7), the hot roller pressure is 0.45-0.55 MPa and the temperature range is 146-167°C.
10. The method according to claim 1, characterized in that In step (8), the drafting is 3.3 to 3.5 times.
Citation Information
Patent Citations
Preparation method for polyacrylonitrile-based carbon fiber protofilament
CN102953143A
Preparation method for polyacrylonitrile-based carbon fiber protofilament
CN102953144A
Preparation method for vitriolization irradiation modified polyacrylonitrile pre-oxidation fiber
CN106192362A
Process of durable and conductive fibre
CN87104346A
Method for producing flame retardant fiber and carbon fiber
JP2007186802A
